The 2017 Joint Review of the Standards and Codes Initiative. (Policy Papers; Policy Paper ;, 2017)
The standards and codes (S and C) initiative was launched in the aftermath of the emerging market crises of the 1990s as part of efforts to strengthen the international financial architecture, with a focus on emerging markets. The initiative has aimed at promoting international standards and codes to improve economic and financial resilience by assisting countries in strengthening their economic institutions and informing World Bank and IMF work. The four previous reviews confirmed a fairly high appreciation of the overall initiative, while also raising questions about the initiative's link to surveillance and capacity development efforts, weak uptake by market participants, as well as a need to improve traction with policy makers. This review reaffirms the country authorities' appreciation for S and C work, and its focus and scope are guided by the February 2017 paper.